(untitled) (Czech Journal of International Relations, 2024)
Zsolt Bárány: born in 1969, Hungarian foreign graduate of the University of Economics in Prague in the field of international studies Business/Politics. Milan Kasimír: born 1969, graduate of the University of Economics in Prague, majoring in International Business/Politics.